Mixed messages: An evaluation of NHS Trust Social Media policies in the North West of England. Issue 3 (August 2017) - Scragg, B.; Shaikh, S.; Robinson, L.; Mercer, C.
Abstract: Introduction: Despite National Health Service (NHS) information strategy promoting the use of Social Media (SoMe) to encourage greater engagement between service users and providers, a team investigating online SoMe interaction between breast screening practitioners and clients found that practitioners alleged discouragement from employers' policies. This study aimed to investigate whether this barrier was genuine, and illuminate whether local policy differed from national strategy. Method: The study used a qualitative grounded theory approach to generate a theory. Nine policies from the North West of England were analysed. A framework was derived from the data, and an analysis of policy tone followed by a detailed coding of policy content was undertaken. Comparative analysis continued by reviewing the literature, and a condensed framework revealed five broad categories that policies addressed. Results: The analysis revealed the policies varied in content, but not in tone, which was mostly discouraging. Coding the content revealed that the most frequently addressed point was that of protecting the employers' reputation, and after further analysis, the resultant condensed framework showed that policies were imbalanced and heavily skewed towards Security, Conduct & Behaviour and Reputation. Conclusion: Practitioners within breast screening services are discouraged by overly prohibitive and prescriptive SoMe policies; with these varying tremendously in comprehensiveness, but with a narrow focus on security and employers reputation; in contrast with national strategy. Recommendations are that policy revision is undertaken with consultation by more than one stakeholder, and SoMe training is offered for all members of NHS staff. Highlights: Practitioners are discouraged from using SoMe by employers' policies. This is at odds with national strategy of engagement with all stakeholders. Policies are skewed towards protecting reputation and security measures. Local priorities should re-align with national priorities to encourage SoMe use.